Case study of chicken slaughterhouse / Mohd. Hezri Mansor, Muhammad Roslan Rahim and Mohd Adi Hazly Sa'im - Mansor, Mohd. Hezri; Rahim, Muhammad Roslan; Sa’im, Mohd Adi Hazly (2005)
A slaughterhouse, also called an abattoir (from the French word abattre meaning "to strike down"), is a facility where farm animals are killed and processed into meat products. The animals most commonly slaughter for food are cattle (beef & veal), sheep (lamb & mutton), pigs (pork), poultry and horses (mostly in europe). Many people find the subject of animal slaughter to be very unpleasant and prefer not to know the details of what goes on inside a slaughterhouse. In their turn, most slaughterhouses are secretive to avoid controversy. Nevertheless, the majority of people in the West eat meat every day, so slaughterhouses are required to efficiently provide meat products on an industrial scale. At the same time, most countries have laws and regulations that control the slaughter of animals, both for human consumption and for other purposes. Therefore, the operation of slaughterhouses is usually independently monitored by government agencies, most especially to ensure that standards of hygiene are maintained. Base on this, our group like to do the reaseach of good layout design for small operation slaughterhouse and propose it in our final project for subject KJP 365